1997
DOI: 10.1002/eji.1830270526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin‐10 on dendritic cell maturation and function

Abstract: The main function of dendritic cells (DC) is to induce the differentiation of naive T lymphocytes into helper cells producing a large array of lymphokines, including interleukin (IL)-2; interferon-gamma (IFN-gamma), IL-4, IL-5 and IL-10. The potent immunostimulatory properties of DC develop during a process of maturation that occurs spontaneously in vitro. Since IL-10 has been shown to inhibit Th1 responses, we determined its effect on DC maturation and accessory function. Our data show that DC that have under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
321
1
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 495 publications
(349 citation statements)
references
References 46 publications
25
321
1
2
Order By: Relevance
“…In particular, injection of splenic DCs has been shown to induce the activation of T cells that secrete a large array of cytokines 3 17. Because DCs are the APCs of the primary immune response, we analyzed the adjuvant function of DCs purified from control and μMT mice.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, injection of splenic DCs has been shown to induce the activation of T cells that secrete a large array of cytokines 3 17. Because DCs are the APCs of the primary immune response, we analyzed the adjuvant function of DCs purified from control and μMT mice.…”
Section: Resultsmentioning
confidence: 99%
“…Although we do not have direct evidence, several features suggest that IL-10 may be involved in this immunoregulatory process: splenocytes from μMT mice express reduced levels of IL-10 mRNA than wild-type animals; DCs from IL-10 knockout mice display properties similar to DCs from μMT mice, i.e., they have lost the capacity to induce the development of IL-4–secreting cells; treatment of DCs from μMT mice with IL-10 restored the generation of IL-4–producing cells in vivo; and numerous reports have shown that IL-10 inhibits the production of IL-12 heterodimer by DCs in vitro and in vivo 3 10. Collectively, these observations suggest that the level of IL-12 released by DCs is regulated by B lymphocytes, presumably via the production of IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations